Exergoeconomic power cost rates model for onshore and offshore gas turbines - Majid, M.A.A. (Asian Research Publishing Network, 2016)
Both the onshore and offshore power generating plants use gas turbines for power generation. The normal practice is to evaluate feasibility of the plants using rate of return approach. This approach does not incorporate the energy and exergy analysis. The more appropriate approach is to apply the exergoeconomic method. By adopting this method both the economic as well as exergetic analysis are incorporated in the evaluation. This study investigated the application of exergoeconomic method to evaluate the cost rates of electricity produced by the gas turbines for both the onshore and offshore power generating plants. The methodology incorporates cost rates associated to capital investment, operation and maintenance and exergy transfers into and out of the turbine. The cost rates for the capital investment of the turbine cover the capital recovery cost. The cost rates for the operations cover the fuel cost and the maintenance cost rates cover the maintenance cost throughout the whole life of the turbine. The cost rates associated with exergy transfers include all the cost rates due to entering and exiting material streams as well as both heat and work interactions with the surrounding and exergy destructions. Data for the study were obtained from the operating onshore and offshore gas turbines. The exergetic cost rates were established using the first and second law themodynamics. EES and Mathlab were used to analyse the model. In both cases the cost rates decrease with increased of power output assuming ten per cent interest rates and service life of twenty years. For future study sensitivity analysis on interest rates, service life, CAPEX and OPEX will be done. The model could them provides more accurate costing of power rates for industrial application. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.